Kritik Terhadap Ajaran Keselamatan Kristen Progresif Berdasarkan Kisah Para Rasul 4:12 - Halawa, Juliusman (Sekolah Tinggi Teologi Baptis Indonesia, 2024)
One of the important concepts in Christian theology is salvation, which has been a subject of discussion and interpretation. Using Acts 4:12 as the main point, this article examines progressive Christian teachings on salvation. The statement that